Analysis and Design of the Mentor On-Demand Service Interface Using the Design Thinking Method - Eristya Maya Safitri; Khalid Rijaluddin (International Journal of Computer, Network Security and Information System, 2023)
Skilvul is a technology education platform that provides digital skills learning content by applying blended learning methods in online and offline forms. The skilled platform will develop a feature, namely mentor on demand, where the mentee can provide guidance and solve problems faced by being accompanied by a mentor privately. In general, online learning is carried out concurrently so the large ratio of mentors to students in a virtual class causes limited mentor communication with each student. This makes students feel that they are not fully guided by mentors because of the large number of students in one virtual class. The interface design process for the mentor-on-demand feature uses the design thinking method. This method has 5 stages, namely empathize, define, ideate, prototype, and testing. Testing is carried out on prototypes that have been generated using the SEQ metric. The average value of SEQ is at number 6 on a scale of 1 to 7. This can be interpreted that the prototype made can be easily understood by users so that problems related to online learning can be resolved